Cohesin is required for expression of the estrogen receptor-alpha (ESR1) gene - Prenzel Tanja; Kramer Frank; Bedi Upasana; Nagarajan Sankari; Beissbarth Tim; Johnsen Steven A (Epigenetics & Chromatin, 2012)
Abstract Background In conjunction with posttranslational chromatin modifications, proper arrangement of higher order chromatin structure appears to be important for controlling transcription in the nucleus. Recent genome-wide studies have shown that the Estrogen Receptor-alpha (ERα), encoded by the ESR1 gene, nucleates tissue-specific long-range chromosomal interactions in collaboration with the cohesin complex. Furthermore, the Mediator complex not only regulates ERα activity, but also interacts with the cohesin complex to facilitate long-range chromosomal interactions. However, whether the cohesin and Mediator complexes function together to contribute to estrogen-regulated gene transcription remains unknown. Results In this study we show that depletion of the cohesin subunit SMC3 or the Mediator subunit MED12 significantly impairs the ERα-regulated transcriptome. Surprisingly, SMC3 depletion appears to elicit this effect indirectly by rapidly decreasing ESR1 transcription and ERα protein levels. Moreover, we provide evidence that both SMC3 and MED12 colocalize on the ESR1 gene and are mutually required for their own occupancy as well as for RNAPII occupancy across the ESR1 gene. Finally, we show that extended proteasome inhibition decreases the mRNA expression of cohesin subunits which accompanies a decrease in ESR1 mRNA and ERα protein levels as well as estrogen-regulated transcription. Conclusions These results identify the ESR1 gene as a cohesin/Mediator-dependent gene and indicate that this regulation may potentially be exploited for the treatment of estrogen-dependent breast cancer.